2013
DOI: 10.14233/ajchem.2013.15237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corrosion Inhibition Performance of Zinc Oxide and Sodium Nitrite in Quarry Dust Concrete

Abstract: The objective of this study is to discuss the inhibitive behaviour of two inorganic corrosion inhibitors namely sodium nitrite, an anodic inhibitor and zinc oxide, a cathodic inhibitor on steel embedded in concrete containing quarry dust as fine aggregate. Each inhibitor was evaluated for various strength properties such as compressive strength, split tensile strength, flexural strength and bond strength in addition to water absorption capacity. The performance of the inhibitors on corrosion resistance was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Similarly, it has been shown that ZnO could reduce the voids within cement composite (Behfarnia and Keivan, 2013). This has been highlighted by extensive research on corrosion inhibition performance of Sodium Nitrite and Zinc Oxide in concrete mixes (Devi and Kannan, 2013). Additionally, studies have shown that incorporation of ZnO reduced the corrosion effect on concrete (Saraswathy and Song, 2007;Nivethitha and Dharmar, 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, it has been shown that ZnO could reduce the voids within cement composite (Behfarnia and Keivan, 2013). This has been highlighted by extensive research on corrosion inhibition performance of Sodium Nitrite and Zinc Oxide in concrete mixes (Devi and Kannan, 2013). Additionally, studies have shown that incorporation of ZnO reduced the corrosion effect on concrete (Saraswathy and Song, 2007;Nivethitha and Dharmar, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…5 bars of pressure was retained during the tests for a period of 72 hours. The maximum water penetration level was observed from the burette tank and the concrete cube (Erhan, 2014). The samples were taken after 28 days and 56 days of concrete.The tested result shows (Fig.…”
Section: Water Permeability Testmentioning
confidence: 99%
“…Corrosion inhibitors, which can effectively prevent the corrosion of steel bars, are widely used in the concrete industry (Ormellese et al, 2011;Aydin and Cizmeciglu, 2015;Diamanti et al, 2017;Sun et al, 2019). The widely used corrosion inhibitors include phosphate (Mandal et al, 2020), chromate (Schiessl et al, 2008;Okeniyi et al, 2014), zinc oxide (Devi and Kannan, 2013), gluconate (Li et al, 2015), amines (Qian and Cusson, 2004), nitrite (Krolikowski and Kuziak, 2011;Mandal et al, 2020), and so on (Soylev and Richardson, 2008). Gonzalez compared the different corrosion inhibitors and found that nitrite corrosion inhibitors have a more significant corrosion inhibiting effect than the others (González et al, 1998).…”
Section: Introductionmentioning
confidence: 99%